LIGHT-EMITTING DIODE (LED) AND LASER GAS ANALYSERS FOR IMPROVING EFFICIENCY OF FUEL BURNING IN HEAT POWER ENGINEERING - V. A. Firago; S. N. Drozd; V. Voujtsik; M. M. Kougejko; I. S. Manak (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2005)
The paper contains estimation of threshold sensitivity of correlation measuring methods in light-emitting diode and laser devices for continuous control of boiler smoke gas composition. Proposals are given to eliminate influence of dissipation losses and instability of optic and electronic path parameters on the results of control process. It is shown that application of non-dispersion and modified correlation methods for measuring CO and O2 concentration and infra-red light-emitting diodes lasers make it possible to conduct continuous control of smoke gas composition. This control is made by means of smoke flow exposure without taking samples and ensuring small errors and operational reliability.